ORGANOGENESIS AND GENETIC TRANSFORMATION OF YELLOW PASSION FRUIT (Passiflora edulis f. flavicarpa DEG.) WITH THE GENES CMe-ACO1 AS AND nptII THROUGH Agrobacterium tumefaciens - WINKLER, Larissa Macedo (Scientia Agraria, 2002)
Brazil is the main world producer of yellow passion fruit (Passiflora edulis f. flavicarpa). Fruits have a great nutritive and pharmaceutic value. They are commercialized in natura and industrialized for national market and exportation. Passion fruits present a high loss of water during fruit ripening, what is a concern for transport. In order to improve fruit quality and storage life, experiments were carried out for regeneration of plants from leaf explants of Passiflora edulis and for introduction of an antisense melon ACCoxidase gene (LEM1) via Agrobacterium tumefaciens strain carrying binary vectors. During climateric fruits ripening process, like yellow passionfruit, 1-carboxylic-1-aminocyclopropane (ACC) is converted into ethylene by the action of ACCoxidase enzyme. Two regeneration experiments were conducted, using Murashige and Skoog (1962) as basic medium. The effect of several factors was evaluated: physiological age of the explants (juvenile and adult), position of the explant on culture medium (with abaxial or adaxial face in contact with the medium), and three concentrations of benzyladenine (BAP) (1.0, 1.5 and 2.0 mg.L-1). The following data were recorded: percentage of regenerating leaf explants, mean number of buds per explant, mean number of leaves, mean length of the regenerated shoots and percentage of explants forming calli. Every experiment was repeated twice, each treatment had four repetitions of ten leaf explants each. The concentration of 1.5 mg.L-1 originated the best results for all the recorded datas for both positions and for juvenile and adult material. Callogenesis was high in the presence of 2 mg.L-1 BAP. For juvenile material grown from seeds, 50,22% of the explants formed adventitious buds by organogenesis for both positions of the explants. For adult material, IAPAR genotypes 309, 156 x 123 and 352 originated the highest percentages of adventitious buds when cultivated with adaxial face in contact with the medium. Elongation and rooting of the regenerated shoots were obtained in the presence of MS medium or half-strength salts of MS medium and 1 mg.L-1 of gibberellic acid. However, stem size, mean root number, and size were higher on the half strenght of MS salts. Through transformation experiments, leaf explants were co-cultured with disarmed A. tumefaciens vector pGA643 carrying LEM1 gene and EHA101 strain containing a plasmid harbouring a NOS/NPTII gene. Three plants among nine growing in the presence of kanamycin were transformed with NPTII gene, and one plant among six growing in the presence of kanamycin contained LEM1 gene, with 4.3% and 1.43% of transformation efficiency, respectively, as indicated by PCR analysis. Colorimetric analysis of commercial fruits allowed to classify them into three groups: mainly green, mainly colored and partially colored. Ethylene production and enzymatic activity of ACCoxidase were measured and indicated that yellow passion fruit is an intermediary producer of ethylene and that ACCoxidase has a limited activity and needs cofactors to reach a maximum value.